The history of anatomy and the practice of anatomy (including imaging) - Nicholson, Helen (Henry Stewart Talks, 2023)
History of anatomy, Microscopy, Cadavers, Imaging: MRI, CT, ultrasound, Acquisition of human cadavers, Body donation, Dissection, Studying anatomy, Grave robbers, Anatomical models, plastination and wax models